Longing for the Lost Caliphate: A Transregional History By Mona Hassan (Princeton, NJ: Princeton University Press, 2016. 409 pages.) (American Journal of Islam and Society, 2019)
In her superbly learned book, Mona Hassan sets out to explain the enduring meaning of Muslim lamentations after two of the greatest Muslim caliphates were abolished in 1258 and 1924 CE. 1258 marks the date when the last Abbasid Caliph, al-Musta‘sim, knelt before the Mongol Commander Hulegu outside the walls of Baghdad, shortly before he was executed. Hassan is not here directly concerned with the history of either the Abbasid Caliphate or the Mongol conquest; rather, she seeks to understand what was a novel problem for the Muslim community, namely, the absence of a caliph, which then lasted three and a half years.